Functional Applications of Future Data Storage Devices. (12th March 2021) - Yang, Jia‐Qin; Zhou, Ye; Han, Su‐Ting
Abstract: The development of artificial intelligence and big data analytics is driving a revolution in methods for data processing and storage. Confronting speed and energy consumption issues, these fields require new computing systems to parallelly retrieve, process, and store massive amounts of data. Beyond CMOS devices and technology, advances in data storage technology such as static random‐access memory, dynamic random‐access memory, flash memories, resistive memories, phase change memories, and magnetic memories have made functional computing possible. In this article, a broad overview of current memory systems and their development history spanning fundamental operating schemes, prevailing applications and required figure of merits for applications such as in‐memory computing and some critical issues that need to be addressed in the future development of this emerging technique are provided. Abstract : Future memory technologies introduce computation into memory to reduce the frequent movement of data on the bus, providing new insights for building high‐efficiency computing systems. This paper provides an overview of related work in various memory techniques, their applications, and required parameters in in‐memory computing, the current state of the art, and evaluation metrics and highlights opportunities for further development.